SOSIALISASI PENCEGAHAN DAN DAMPAK NARKOBA BAGI GENERASI MUDA KHUSUSNYA PELAJAR - Rina hayati Maulidiah; syahriani sirait; Siska Silvia; Julia Anggreyni (Smart Education, 2024)
This study discusses the socialization of drug prevention and impacts for the younger generation, especially students. The main objective of this socialization is to provide a comprehensive understanding of the dangers of drugs, both physically, mentally, socially, and legally, and to encourage students to avoid such risky behavior. The socialization method involves educational activities such as seminars, counseling, and interactive discussions attended by students, teachers, and parents. The results of the study show that consistent and comprehensive socialization is effective in increasing students' awareness of the risks of drugs, as well as strengthening their resilience to reject negative influences. In addition, the involvement of the school and family environment plays a significant role in providing support for students to build a drug-free environment. Thus, drug prevention socialization is an important step in maintaining the health of the younger generation and preparing them as superior human resources.